United Nations Peace Operations in a Changing Global Order - de Coning, Cedric; Peter, Mateja (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
"This book is essential for enhancing one's understanding of international conflict and for the continued relevance of the UN as a key stakeholder and participant in world affairs." -Maj. Gen. Kristin Lund, Head of Mission and Chief of Staff, UN peacekeeping mission in the Middle East (UNTSO) "This outstanding collection is a must-read for anyone interested in the challenges of peacekeeping today." -Dr. Lise Howard, Georgetown University, USA "I would recommend this book to policy makers, peacekeepers and scholars who wish to understand and improve the effectiveness of modern peacekeeping." -Lt. Gen. Carlos Alberto dos Santos Cruz, former Force Commander in the UN missions in the DRC (MONUSCO) and Haiti (MINUSTAH) "This exceptional collection of analyses by experts from both the global North and South will be of interest to practitioners and scholars alike - highly recommended." -Prof. Ramesh Thakur, Australian National University This open access volume explores how UN peace operations are adapting to four trends in the changing global order: (1) the rebalancing of relations between states of the global North and the global South; (2) the rise of regional organisations as providers of peace; (3) the rise of violent extremism and fundamentalist non-state actors; and (4) increasing demands from non-state actors for greater emphasis on human security. It identifies emerging conflict and peace trends (robustness of responses, rise of non-state threats, cross-state conflicts) and puts them in the context of tectonic shifts in the global order (rise of emerging powers, North-South rebalancing, emergence of regional organisations as providers of peace). The volume stimulates a discussion between practitioners and academics, offering an analysis of how the international community collectively makes sense of the changing global order and its implications for UN peace operations. Cedric de Coning is Senior Research Fellow at the Norwegian Institute of International Affairs (NUPI), Norway and Senior Advisor for the African Centre for the Constructive Resolution of Disputes (ACCORD), South Africa. Mateja Peter is Lecturer at the University of St. Andrews, UK and Senior Research Fellow at the Norwegian Institute of International Affairs (NUPI), Norway.